The Effect of Agonists and Antagonists of Platelet Aggregation on von Willebrand Factor-Mediated Platelet Agglutination - McPherson, Jean; Zucker, Marjorie B; Mauss, Evelyn A; Brownlea, Sandra (Thrombosis and Haemostasis, 1991)
Ristocetin-induced platelet agglutination (RIPA) in EDTA-treated citrated platelet-rich plasma was reduced to 49 ± 11% by 1.25 ΜM ADP, 41 ± 14% by 1 ΜM A 23187, and 26 ± 7% by 0.1 Μg/ml platelet activating factor (PAF). The effect of 5-110 ΜM epinephrine was not dose-dependent, but varied between donors, with RIPA from 56-100% of the control. The inhibitory effects of these agonists were not altered by prior treatment of platelets with aspirin. Prior addition of 200 ΜM ATP (an ADP receptor antagonist acting at both high and low affinity ADP receptors) prevented the inhibitory action of ADP but not that of A 23187 or PAF, suggesting that the inhibitory actions of the latter are not mediated by released ADP. As 700 ΜM 8-bromoadenosine 5-diphosphate (an ADP receptor antagonist acting mainly at the high affinity receptor) did not prevent ADP-induced inhibition of RIPA, interaction of ADP with the low affinity receptor is presumably responsible for its inhibitory action. As A 23187, but not phorbol myristate acetate (0.1 ΜM) inhibited RIPA, an increase in intracellular calcium ions rather than direct stimulation of protein kinase C appears to mediate agonist-induced inhibition. Cytochalasin B (10.5-21 ΜM), dibucaine (0.5-1 mM), and prostaglandin E1 (25 nM), added before or after the agonist, prevented or reversed ADP-, A23187-, and PAF-induced inhibition of RIPA, suggesting that the state of the platelet cytoskeleton affects inhibition. N-ethylmaleimide (0.25-0.5 mM), an agent that can penetrate cell membranes and block sulphydryl groups, prevented or reversed ADP, A 23187- and PAF-induced inhibition of RIPA, but 0.5 mM dithionitrobisbenzoic acid, a non-penetrating sulphydryl blocker, had no effect. Diamide (0.1-0.5 mM), an agent that can crosslink cytoskeletal proteins by oxidation of sulphydryl groups, reduced RIPA. Thus an increase in intracellular calcium ions with resultant cytoskeletal changes and reorganisation of intracellular sulphydryl groups may mediate the inhibitory action of agonists on RIPA.